Changes in the morphology traits, anatomical structure of the leaves and transcriptome in Lycium barbarum L. under salt stress - Yao, Xiao-Cui; Meng, Li-Fang; Zhao, Wang-Li; Mao, Gui-Lian (Frontiers in Plant Science, 2023)
Salt stress directly affects the growth of plants. The limitation of leaf grow is among the earliest visible effects of salt stress. However, the regulation mechanism of salt treatments on leaf shape has not been fully elucidated. We measured the morphological traits and anatomical structure. In combination with transcriptome analysis, we analyzed differentially expressed genes (DEGs) and verified the RNA-seq data by qRT-PCR. Finally, we analyzed correlation between leaf microstructure parameters and expansin genes. We show that the leaf thickness, the width, and the leaf length significantly increased at elevated salt concentrations after salt stress for 7 days. Low salt mainly promoted the increase in leaves length and width, but high salt concentration accelerated the leaf thickness. The anatomical structure results indicated that palisade mesophyll tissues contribute more to leaf thickness than spongy mesophyll tissues, which possibly contributed to the increase in leaf expansion and thickness. Moreover, a total of 3,572 DEGs were identified by RNA-seq. Notably, six of the DEGs among 92 identified genes concentrated on cell wall synthesis or modification were involved in cell wall loosening proteins. More importantly, we demonstrated that there was a strong positive correlation between the upregulated EXLA2 gene and the thickness of the palisade tissue in L. barbarum leaves. These results suggested that salt stress possibly induced the expression of EXLA2 gene, which in turn increased the thickness of L. barbarum leaves by promoting the longitudinal expansion of cells of the palisade tissue. This study lays a solid knowledge for revealing the underlying molecular mechanisms of leaf thickening in L. barbarum in response to salt stresses.